2005
DOI: 10.4049/jimmunol.174.5.2702
|View full text |Cite
|
Sign up to set email alerts
|

Two Structurally Related Rat Ly49 Receptors with Opposing Functions (Ly49 Stimulatory Receptor 5 and Ly49 Inhibitory Receptor 5) Recognize Nonclassical MHC Class Ib-Encoded Target Ligands

Abstract: The Ly49 family of lectin-like receptors in rodents includes both stimulatory and inhibitory members. Although NK alloreactivity in mice is regulated primarily by inhibitory Ly49 receptors, in rats activating Ly49 receptors are equally important. Previous studies have suggested that activating rat Ly49 receptors are triggered by polymorphic ligands encoded within the nonclassical class Ib region of the rat MHC, RT1-CE/N/M, while inhibitory Ly49 receptors bind to widely expressed classical class Ia molecules en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 53 publications
(75 reference statements)
2
47
0
Order By: Relevance
“…We have recently shown that some inhibitory and activating Ly49 receptors are coexpressed in certain subsets of rat NK cells (11). A striking finding in the present study is that NKR-P1C was expressed mainly by the Ly49-negative fraction of NK cells.…”
Section: The Nkr-p1csupporting
confidence: 67%
See 2 more Smart Citations
“…We have recently shown that some inhibitory and activating Ly49 receptors are coexpressed in certain subsets of rat NK cells (11). A striking finding in the present study is that NKR-P1C was expressed mainly by the Ly49-negative fraction of NK cells.…”
Section: The Nkr-p1csupporting
confidence: 67%
“…The precise contribution of inhibitory and activating Ly49 and KIR receptors to NK-mediated alloreactivity remains to be determined. Studies in rats have pointed toward a central role for the activating receptors (10,11). Therefore, it is possible that transplant patients lacking activating KIRs have a reduced risk of rejection of NK-incompatible (KIR/HLA) stem cell grafts in the clinical setting, especially under nonmyeloablative regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlapping specificity of activating and inhibitory pairs is a common theme for several MHC-binding NK receptors including Ly49, KIR, and CD94/NKG2 [28][29][30][31]. The basis for the development of parallel inhibitory and activating NKR-P1 recognition systems for the same ligands is not clear, but the existence of viral Clr decoys [23] suggests that it may be pathogen-driven.…”
Section: Discussionmentioning
confidence: 99%
“…in the context of inflammation and transplantation. These tasks are controlled by a wide range of receptors with different functions and ligands, such as Ly49 receptors, which recognize both classical and nonclassical MHC class I molecules, as well as MHC Correspondence: Dr. Lise Kveberg e-mail: lise.kveberg@rr-research.no class I-like virally encoded ligands [1][2][3]. Another family of MHCbinding receptors is the conserved NKG2/CD94 heterodimers, which bind the nonclassical MHC molecule HLA-E in human [4], its rodent homologue Qa-1 b in the mouse [5,6] and RT.BM1 in the rat [7].…”
Section: Introductionmentioning
confidence: 99%